Application of Normal and Derivative Ultraviolet Absorption Spectroscopy for the Determination of Six Polyaromatic Hydrocarbons in Tigris River - Abdul Latif M. Raouf, et.al (Al-Qadisiyah Journal of Pure Science, 2017)
The aim of this study is to find a suitable analytical method for determination of some polyaromatic hydrocarbons (PAHs) in different locations in Tigris river. Six of PAHs are studied according to Environment Protection Agency, which are Naphthalene, Anthracene, Acenaphthene, Acenaphthylene, Phenanthrene, and Fluorene. Ultraviolet - Visible technique is applied by using normal and derivative spectra to find a suitable wavelength for qualitative and quantitative measurements for each compound. The calibration curve for the standard solution for the six PAHs (0.1-100) ppm gave linearity (0.979-0.999).The proposed method was applied on different samples from Tigris river. High level of contamination caused by PAHs was detected in these samples in comparison with a previous study.